Not only sagas: The Early History of Norway in medieval Monuments. - Scheglov, Andrey (Collegium Medievale, 2019)
The interest towards sources on early Norwegian history is traditional for Russia, and Russian specialists on Viking and Medieval Norway, such as Mikhail Steblin-Kamensky, Aron Gurevich, Elena Mel'nikova and Tatyana Dzhakson are known both in Russia and abroad. However, these scholars have mainly focused on the sagas. As a result, Norwegian chronicles are less familiar to the Russian audience. The anthology "Not only sagas…" fills this gap.